PENGARUH E-SERVICE QUALITY DANE-SATISFACTIONTERHADAPE-LOYALTY: Studi pada Pelanggan Situs Jual Beli Shopee di Purworejo (STIE Rajawali Purworejo, 2021)
This research aims to find out whether partially and simultaneously there is a positive and significant influence between e-service quality and e-satisfaction on e-loyalty among customers of the Shopee buying and selling site in Purworejo. The data source uses a questionnaire. The population in this study are customers who have purchased more than 3 times on the Shopee buying and selling site in Purworejo. The sampling technique used was purposive sampling. The sample used was 30 people. The data analysis techniques used are validity test, reliability test, multiple regression analysis, coefficient of determination, t test and F test. The results of the validity test prove that all the statement items for the variables e-service quality, e-satisfaction and e-loyalty show a Pearson correlation value of more than 0.3. The results of the reliability test show that the Cronbach's alpha value for the e-service quality, e-satisfy action and e-loyalty variables is more than 0.70. The results of multiple linear regression analysis show: a) a constant of 0.672; b) b1 value of 0.122; c) b2 value of 0.743. The results of the coefficient of determination show an AdjustedRsquare value of 0.953. This means that e-service quality and e-satisfaction contribute 95.3% to e-loyalty. The t test results show: a) the t value of the e-service quality variable is greater than t table (2.370 > 1.699) or a sig value of 0.025 (p < 0.05); b) the tcount value of the e-satisfaction variable is greater than ttable (3.747 > 1.699) or the sig value is 0.001 (p < 0.05). The results of the F test show that the F value is 292.628, which is greater than 4, and the sig value is 0.000 (p < 0.05).